Dynamics of Parent Engagement in Preschool - Venugopal, Kalpana (JOURNAL OF INDIAN EDUCATION, 2017)
This is a narrative of the engagement of parents and family in a preschool. The purposive strategy of action planned in the study is detailed. It entails vivid descriptions of creative ideation, designing, development and process of parent and family involvement in supporting school activities and initiatives. The discussion that ensues draws on the underpinnings to establish the implication of meaningful engagement between the home and the school.